2011
DOI: 10.1186/1471-2458-11-600
|View full text |Cite
|
Sign up to set email alerts
|

Are skin disorders related to work strain in hospital workers? A cross-sectional study

Abstract: BackgroundTo evaluate whether occupational stress factors (high demands, low control, low social support, strain, and iso-strain) are associated with skin disorders in hospital workers and whether psychological problems, such as anxiety and depression, act as potential mechanisms through which occupational stress factors are associated with skin disorders.Methods1,744 hospital workers were invited to answer a questionnaire concerning the occurrence of skin disorders and psychosocial factors at work. The abbrev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…Anxiety and depression are common mental health issues in many first responders including nurses and allied health professionals (Magnavita, 2009; Magnavita et al., 2011, 2020; Magnavita & Fileni, 2014; Magnavita & Heponiemi, 2011). Work impairment, which refers to impairments at work (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety and depression are common mental health issues in many first responders including nurses and allied health professionals (Magnavita, 2009; Magnavita et al., 2011, 2020; Magnavita & Fileni, 2014; Magnavita & Heponiemi, 2011). Work impairment, which refers to impairments at work (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, somatization may render the person unaware of the hidden mental disorder making them seek help for these symptoms alone leaving depression untreated [ 9 , 10 ]. Indeed, depressive symptoms are significantly associated with physical work-related symptoms in indoor workers [ 11 ] with musculoskeletal symptoms in health social care workers [ 12 ] and with skin symptoms in health care workers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Wen-Qing Li et al found an association between inflammatory skin disease (psoriasis) and night shift postulating that the increased risk could be related to a diminished ability of the pineal gland to produce melatonin (19). Furthermore, we have to consider the possible role of occupational stress, related to the work strain of HCWs, in the development of skin disorders according to data from literature (20,21).…”
Section: Discussionmentioning
confidence: 99%